THE INFLUENCE OF BEHAVIORAL FINANCE ON RISK TAKING BEHAVIOR AMONG RETAIL INVESTORS - Rosid, Abdul (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Risk-taking behavior among retail investors is often influenced by psychological factors, including heuristics, emotions and overconfidence. Understanding the interactions between these factors is critical to improving investment decisions and reducing the risk of financial loss.This research aims to explore the influence of heuristics, emotions and overconfidence on risk taking by retail investors, as well as how these three factors interact with each other in the context of investment decision making. This research uses a Systematic Literature Review (SLR) approach with the PRISMA method to identify, assess and analyze 40 relevant articles. Data were collected from Scopus and Web of Science databases, and analysis was carried out using thematic analysis techniques to identify main patterns and themes. Findings show that heuristics such as anchoring and availability bias, as well as emotions such as fear and greed, significantly influence investment decisions. Overconfidence has also been proven to increase investors' tendency to take higher risks, often without adequate analysis.This research provides important insights into how psychological factors influence retail investment behavior. These findings contribute to the development of behavioral finance theory and offer practical implications for financial service providers in designing more effective strategies to help investors manage their psychological biases.